Comparison of the sensitivities of two 4DCT techniques: RPM and bellows system. (29th March 2012) - Mizuno, Kazue; Song, Yulin; Obcemea, Ceferino
In modern radiation therapy, the target motion caused by respiration could result in a geometric miss of the target and severe damage to the surrounding critical organs and normal tissues. To tackle this issue, various 4D Radiation Therapy (4DRT) techniques have recently been proposed and developed, among which the Real-time Position Management System (RPM) and the Bellows system are the most commonly used 4DRT approaches. Nevertheless, a systematic comparison of these two has not been conducted. In this study, we compared the clinical performance of the RPM and the Bellows system by using a newly developed breathing phantom.